PERAN BP4 DALAM PEMBENTUKAN KELUARGA SAKINAH (Studi Analisis di KUA Kecamatan Ciamis Kabupaten Ciamis) - Siti Ulfah; Pepe Iswanto (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2018)
The formation of a sakinah family is the essence of the purpose of marriage. The process of forming a sakinah family is not an easy thing, it needs sufficient knowledge, mental and material skills to build it. In addition, there needs to be support and participation from outside such as from related institutions, in this case BP4. The problems that arise are, first, what is the role of BP4 KUA in Ciamis District in forming sakinah families. Second, what are the obstacles for the Ciamis District BP4 KUA in forming a sakinah family. Third, what is the action of BP4 KUA Ciamis Subdistrict on the problems faced in forming a sakinah family. This research was conducted to determine the role of BP4 in forming sakinah families in KUA, Ciamis District, Ciamis Regency. Knowing the problems faced by BP4 in forming a sakinah family in KUA, Ciamis District, Ciamis Regency. Knowing BP4's actions in solving problems in the formation of sakinah families in KUA, Ciamis District, Ciamis Regency. The method used in this research is descriptive method, which is a research method that is directed to solve problems that occur at this time, by presenting the results of the research as they are. This is based on a study conducted by researchers, namely to describe the role of BP4 in forming a sakinah family. The conclusion of this study, the role of BP4 in forming a sakinah family is as follows, 1) The role of BP4 in forming a sakinah family will be felt by the community if it is not underestimated. As divorces are rampant, the role of BP4 in this case is very important, its performance must be improved again, so that the community can feel the existence of this institution. 2) The problem faced by BP4 Ciamis Subdistrict in implementing its programs to form a sakinah family is the lack of public understanding of the role of BP4 in the formation of a sakinah family. Socialization runs naturally, meaning that there is no special socialization about institutions. There are no binding rules for prospective brides in the form of sanctions if they do not carry out prenuptial guidance. 3) BP4 Ciamis Subdistrict's actions on the problems faced in the formation of the sakinah family in its implementation provide marriage guidance to prospective brides about marriage, thalak and referencing either individually or in groups. However, the role of BP4 in KUA Ciamis District has not been optimal because even though there is guidance or delivery of information about BP4 at the recitations of the t'alim assembly and related events, in this case there is no enthusiasm from the community. They feel that they have not benefited from the existence of BP4.